Development of soy fortified sorghum and bread wheat biscuits as a supplementary food to combat protein energy malnutrition in young children - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.